Photocatalytic and Antimicrobial Activity of Titanium(IV)-Oxo Clusters of Different Core Structure - Barbara Kubiak; Piotr Piszczek; Aleksandra Radtke; Tadeusz Muzioł; Grzegorz Wrzeszcz; Patrycja Golińska (Crystals, 2023)
The purpose of this paper is to assess the relationship between the core architecture of titanium(IV)-oxo complexes (TOCs) known as TiaOb and their photocatalytic and antimicrobial activity. The following TOCs: [Ti6O4(OiBu)8(O2C13H9)8] · 2(CH3)2CO (1), [Ti6O6(OiBu)6(O2C13H9)6] (2), [Ti6O6(OiBu)6(O2C13H9)6] (3), [Ti3O(OiPr)8(O2C13H9)2] (4), and [Ti4O2(OiBu)10(O2C13H9)2] (5), where -O2C13H9represents 9-fluorene-carboxylate ligands, werestudied to investigate thiseffect. The structures of (1)–(5) were confirmed using single-crystal X-ray diffraction and spectroscopic methods. Since TOCs can be sensitive to hydrolysis processes, their photocatalytic and antimicrobial activity was evaluated after dispersing them in a polymer matrix, which acted as a protective agent against the aquatic environment. The results revealed that the photocatalytic activity of the studied TOCs follows the trend (2) > (5) > (4) > (1) in both the UV and visible ranges. All studied oxo complexes exhibited strong antibacterial activity against Gram-positive strains and weaker activity against Gram-negative strains. The proposed mechanism of the antimicrobial activity of TOCs assumes that this effect is associated with the generation of reactive oxygen species (ROS) on the surface of composite samples. Samples of PMMA + (1) 10 wt.% and PMMA + (5) 20 wt.%, in which both O− and O2− paramagnetic species were observed in the electron paramagnetic spectroscopy (EPR) spectra, demonstrated the highest antimicrobial activity.